Publication of Translations of Modern Mahua Literature in Magazines Published by Dewan Bahasa dan Pustaka (DBP) - Seong, Goh Sang; Ean, Boh Phaik (Malay Literature, 2021)
This article documents the translations of works of modern Mahua literature in magazines published by Dewan Bahasa dan Pustaka (DBP). Discussion is made descriptively, guided by translation history theory employing eight objects of study proposed by D'hulst (2010), i.e. quis (who)?, quid (what)?, ubi (where)?, quibus auxiliis (which sort of support)?, cur (why)?, quomodo (how)?, quando (when)?, and cui bono (what are the effects)? The translations of modern Mahua literature in magazines published by DBP were collected manually from magazines from the collection stored at the National Library of Malaysia (PNM). Data collected were analysed using bibliometric methods. Findings from the study show that the translations of modern Mahua literature were published in Dewan Bahasa and Dewan Sastera comprises 33 poems and short stories. 12 local translators were involved in producing these translations since 1968. The publishing effort of the translation of Mahua modern literary works into Malay aims at introducing Chinese culture and thoughts through Mahua literature to Malay-language readers to promote understanding and cultivate national integration.